WHEN CHRONIC HEPATITIS B TURNS ACUTE: UNDERSTANDING AND MANAGING FLARES - Hartungi, Florean; Christeven, Robert (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Hepatitis B flare is a sudden exacerbation of chronic hepatitis B, defined by an abrupt ALT rise >5× upper limit of normal. Clinically, it may resemble acute hepatitis B, but low IgM anti-HBc titers and high HBV DNA levels aid differentiation. Flares arise from immune-mediated hepatocyte injury, triggered spontaneously, by immunosuppressive or antiviral therapy, pregnancy, viral superinfection, or viral genotype variations. Presentation ranges from asymptomatic biochemical changes to severe hepatitis, coagulopathy, and acute liver failure. Evaluation requires thorough history, physical examination, laboratory testing, imaging, and sometimes liver biopsy. Management focuses on supportive care and early nucleos(t)ide analogue therapy, as interferon can precipitate hepatic decompensation in severe immune-driven flares. Prognosis depends on baseline liver health; patients without cirrhosis generally recover, while acute-on-chronic liver failure carries high short-term mortality and may necessitate liver transplantation. Prompt recognition and timely antiviral therapy are essential to prevent liver failure, highlighting the importance of individualized strategies for optimal outcomes in hepatitis B flares. Keyword: chronic hepatitis B, flare